Cropland Inventory in Chambal Command Area of Rajasthan Using IRS 1C Data - Kumkar, J M; Kumar, Virendra (Journal of Agricultural Engineering, 2004)
A study was undertaken in Chambal command area of Rajasthan for year 1997-98 rabi season on crop discrimination and acreage estimation using IRS 1C LISS III data. The crop discrimination only with the help of spectral responses of wheat and mustard was found difficult. The separation was done based upon the variation in growth stages of these crops. The results when compared with field figures are found deviated by about 10 per cent.